PENGABDIAN KEPADA MASYARAKAT â€œBIMBINGAN IPTEK DAN PELATIHAN PROSES PERKECAMBAHAN BIJI TANAMAN ANDALIMAN (Zanthoxylum acanthopodium DC.)â€ DI DESA SITARATOIT - Batubara, Melvariani Syari; Ginting, Nurmaini; Ariaji, Rizky (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2018)
This community service activity is Science and Technology Guidance and Training of Andaliman Plant Seed Germination Process (Zanthoxylum acanthopodium DC.) In Sitaratoit Village. Andaliman (Zanthoxylum acanthopodium DC.) Is a wild plant found in North Sumatra, Indonesia, the Rutaceae family. The Batak people use the fruit as a spice in their traditional cuisine. Breaking the seed dormancy period of andaliman plants is the initial treatment of the seeds intended to start the germination process, this effort can be in the form of physical, mechanical or chemical treatment. Andaliman plant germination is a process of growth and development of embryos that undergo changes where the plumula grows and develops into stems and radicles into roots. Dormancy is a state of stopping growth experienced by a living organism or its part in response to a condition that does not support normal growth. Thus, dormancy is a reaction to certain physical or environmental conditions. The trigger of dormancy can be mechanical, physical, or chemical. Specific objectives achieved were the provision of science and technology about breaking the seed dormancy period of andaliman plants to the people of Sitaratoit Village, Guidance to the Sitaratoit villagers about the seed germination process of andaliman plants, and the training of Sitaratoit villagers to cultivate andaliman plants. Specific target achieved is that the Sitaratoit Village Community can implement the cultivation activities of andaliman plants, andaliman plants in the Sitaratoit Village area can provide economic benefits for the community, andaliman plant management and cultivation are more noticed and known by the local community, and increase the percentage of seed germination of andaliman plants. The methods used in achieving the objectives of this activity are Village Potential Survey, Conducting dialogues through FGD program activities (Focuss Group Disscussion.), And Science and Technology based guidance and training. The stages of this activity are the Breaking of the Dormancy Period of the Seeds of Andaliman Plants, the Making of Planting Media for the Sprouts of Andaliman Plants, and the Making of the Andaliman Plant Shade. The results of this community service activity are the provision of science and technology about breaking the seed dormancy period of andaliman plants for 2 days to 18 people of Sitaratoit Village, 3 people from the village administration, and 3 students from private universities who are carrying out street vendors activities. The Sitaratoit Village community guidance about the process of seed germination of andaliman plants for 1 day the following day was also actively followed by the Sitaratoit Village community. And the training of the Sitaratoit Village community to cultivate andaliman plants for 1 day after 40 days later has also been carried out well and actively followed by the Sitaratoit Village community.Keywords : Andaliman, Seed dormancy, Seed germination.